2015
DOI: 10.2319/112614-846.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress relaxation in beta-titanium orthodontic loops: Part II

Abstract: Objective: To determine which regions of beta-titanium T-loop springs (TLSs) are more affected by the stress relaxation over a 12-week period. Materials and Methods: Fifty TLS were previously activated by concentrated bends and divided into five groups of 10 each according to their evaluation periods: immediate assessment (G0), 24 hours (G1), 48 hours (G2), 1 week (G3), and 12 weeks (G4). Groups 1 to 4 were mounted into a structure simulating a clinical situation. After the experimental periods, the springs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Curvature was added rather than concentrated bends to the base wire because it has been shown that they may be less sensitive to stress relaxation overtime. 6,23 The M/F produced by the T-loops was different among the groups, which was our most interesting finding since with linear alloys M/F ratios do not appear to change with increased cross section. 18,24 Our results showed similar moments between the two largest wire sizes, but the 0.018" 3 0.025" T-loop showed higher forces, thus having a lower M/F ratio ( Figures 5 through 7).…”
Section: Niti T-loop Wire Dimensions For En Masse Retractionmentioning
confidence: 71%
See 1 more Smart Citation
“…Curvature was added rather than concentrated bends to the base wire because it has been shown that they may be less sensitive to stress relaxation overtime. 6,23 The M/F produced by the T-loops was different among the groups, which was our most interesting finding since with linear alloys M/F ratios do not appear to change with increased cross section. 18,24 Our results showed similar moments between the two largest wire sizes, but the 0.018" 3 0.025" T-loop showed higher forces, thus having a lower M/F ratio ( Figures 5 through 7).…”
Section: Niti T-loop Wire Dimensions For En Masse Retractionmentioning
confidence: 71%
“…23 That large stress concentration induces a stress-induced martensitic transformation that will make that region more flexible rather than more rigid; moreover, further increasing the angulation in that region will cause a different effect than the desired one because higher stresses will make the load/deflection rate of NiTi even lower. 7,21 A solution for that problem has been shown by Bourauel and colleagues 9 with parallel tubes and stainless steel base wires, but that would still allow stress relaxation to occur in that specific region, because there was a 90u bend in the stainless steel base wire after the tubes.…”
Section: Niti T-loop Wire Dimensions For En Masse Retractionmentioning
confidence: 99%
“…This decrease of force over time is in agreement to several other reports that have measured this effect on straight wires, showing it to be time-dependent. 9,11,13 There were only two studies 14 , 18 that looked upon this effect in more elaborate configurations, evaluating stress relaxation on TLSs preactivated by bends, in which a decrease of 15.5% on the force levels of TLSs was shown in the first 24 hours. The present results also show a decrease over time, but with a different behavior that is probably due to the gradual curvature that was used for preactivation, distributing stress over the entire extent of curvature.…”
Section: Discussionmentioning
confidence: 99%
“…Stress relaxation was greatest in T loop springs within 24 hours and gradually increased up to 12 weeks (28). Stress relaxation occurred at the bend between the vertical extensions of the springs and the base arch and the other at the preactivation bends made in the base arch (28).…”
Section: Forum Orthodonticmentioning
confidence: 95%